PROBLEMS FACED BY THE ENGLISH TEACHERS IN INTEGRATING THE BEHAVIOR COMPETENCE TO THE TEACHING OF ENGLISH BASED ON THE 2013 CURRICULUM AT MTsN MODEL MAKASSAR - Ratna Sari Devi (ETERNAL (English, Teaching, Learning and Research Journal), 2015)
This study aims to describe (1) the integration of the spiritual attitude and social attitudes to the teaching of English , (2) the problems faced by English teachers in integrating spiritual attitude and social attitudes to the teaching of English, (3) the English teachers’ effort to cope with the barriers in integrating spiritual attitude and social attitudes to the teaching of English in MTsN Model Makassar.The study was designed in the form of qualitative descriptive study. Subjects in this study were two English teachers in the 7th grade of MTsN Model Makassar. The data were collected by using the methods of documenting, observation, and interviews. Data were analyzed through triangulation data. The results showed that (1) the integration of the behavior competence to the teaching of English lies on the components of planning, implementation, and assessment. The real integration is carried out by means of motivating/encouragement, warning, direction, reprimand, assignment, and reinforcement to students while participating in teaching and learning activity, (2) the obstacles faced by the English teachers (a) difficulty in reconciling the stated in lesson plan and the real activity occured in the classroom (b) difficulty in dealing with different student’s character, (c) lack of time management in teaching, (d) poor management classroom , (e) the lack of infrastructure, (3) the solutions given by the english teachers sharing with Teachers Working Group (KKG), coordinating with teacher counseling  and parents, good teacher-student relationship, and provision of adequate infrastructure.Based on these findings, it can be concluded that the integration of the spiritual attitude and social attitude lies on the components of planning, implementation, and assessment of teaching. Its implementation is done by providing reinforcement  to the internalization of attitudes. The obstacle lies on the planning and implementation. Advice can be given of the results of this research that teachers should more improve the accuracy in selecting the KD of KI-1 and KI-2 to be integrated into the KD of KI-3 and KI-4 in order to enact the planning conform with the implementation. For the education department, they should further enhance the delivery of training related to the implementation of the 2013 curriculum.